Estimation of Jones-Wilkins-Lee parameters of emulsion explosives using cylinder tests and their numerical validation. (December 2018) - Castedo, R.; Natale, M.; López, L.M.; Sanchidrián, J.A.; Santos, A.P.; Navarro, J.; Segarra, P.
Abstract: A microspheres-sensitized emulsion explosive, to be used in rock blasting tests, is characterized by means of the cylinder test. This test measures the expansion of a copper tube upon detonation of an explosive charge inside. Eight cylinder tests have been made with two different diameters (50 mm and 100 mm) and two different densities (1180 kg/m 3 and 1030 kg/m 3 ) in a 2 × 2 × 2 test matrix. The expansion energy is affected by the density but not by the test diameter, which suggests that this explosive, at the densities studied, behaves close to ideal already at 50 mm. The explosive velocity of detonation had been also measured within the trials. In addition, velocities of detonation were measured in six production blasts and reported here. The Jones–Wilkins–Lee (JWL) equation of state parameters have been obtained for this emulsion at the densities and diameters tested. The calculation method includes a radial expansion function, with a non-zero initial velocity at the onset of the expansion. The equations reflecting the CJ state conditions and the measured expansion energy were solved for the JWL parameters by a non-linear least squares scheme. These parameters have been validated with three different LS-DYNA models (Lagrangian-Lagrangian, Smooth Particle Hydrodynamic-Lagrangian, Arbitrary Lagrangian Eulerian-Lagrangian). All models show a good correlation with the test results when comparing them against the detonation pressure, the cylinder wall expansion, the Gurney limit velocities and the radial wall velocities. The Smooth Particle Hydrodynamic is the best numerical model for replicating the detonation pressure, the Lagrangian for the cylinder wall expansion radius and velocity history, and Arbitrary Lagrangian Eulerian on the overall performance. Arbitrary Lagrangian Eulerian and Smooth Particle Hydrodynamic techniques are widely used to describe the materials subjected to large deformations, such as explosives, on full-scale simulations for civil and mining applications. The good agreement between numerical and experimental results justifies the use of these methods to model the expansion of detonation products.